2003
DOI: 10.2320/matertrans.44.681
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Toughness Evaluated by Indentation Methods and Its Relation to Surface Energy in Silicon Single Crystals

Abstract: Fracture toughness of silicon crystals has been investigated by indentation methods, and their surface energy has been calculated using molecular dynamics (MD). When a conical indenter was forced into a (001) silicon wafer at room temperature, {110} cracks were mainly introduced from the indent, indicating that fracture occurs most easily along the {110} plane among the crystallographic planes of the h001i zone. To confirm this orientation dependence, surface energies for those planes were computed using molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
2
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 17 publications
5
14
2
2
Order By: Relevance
“…In all cases, the crack lengths were limited to several micrometers, the median surface breaking cracks always being initiated at the indenter apex. Unlike conical indents [10,11], where it was found that {110} cracks were mainly introduced from the indent, indicating that fracture occurs most easily along the {110} planes among the crystallographic planes of the <001> zone, with Berkovich indents we found no association of the crack geometry with the low surface energy planes. Indeed, ultra-fast X-ray diffraction imaging of fracture in silicon has recently shown that even when cracks are apparently following low energy {110} surfaces, there is a continual jumping between {110} and {111} planes [12].…”
Section: Discussioncontrasting
confidence: 41%
“…In all cases, the crack lengths were limited to several micrometers, the median surface breaking cracks always being initiated at the indenter apex. Unlike conical indents [10,11], where it was found that {110} cracks were mainly introduced from the indent, indicating that fracture occurs most easily along the {110} planes among the crystallographic planes of the <001> zone, with Berkovich indents we found no association of the crack geometry with the low surface energy planes. Indeed, ultra-fast X-ray diffraction imaging of fracture in silicon has recently shown that even when cracks are apparently following low energy {110} surfaces, there is a continual jumping between {110} and {111} planes [12].…”
Section: Discussioncontrasting
confidence: 41%
“…Also, the fracture toughness is in good agreement with the values reported for the macroscale. [21,23,[42][43][44] This demonstrates that the fracture behavior of silicon is not affected by the size and that nanoscale mechanisms govern the macroscale behavior. On this last point, TCD can yield important findings and further results that are detailed in the Discussion section below.…”
Section: Evaluation Of the Nano-si Fracture Toughness By The Tcdmentioning
confidence: 99%
“…Several attempts at measuring the fracture toughness of single-crystal silicon by avoiding the realization of the crack geometry have involved indentation methods. [23] The results, which were obtained through complex molecular dynamics (MD) simulations and by using a large number of samples, did not include any contribution from the plastic work. In summary, cracked specimens are difficult to obtain at the nanoscale, and a large number of samples is needed to obtain a reliable K IC.…”
Section: Introductionmentioning
confidence: 99%
“…As a localized impression testing technique, indentation has been extensively studied for evaluating materials properties such as the modulus [He et al 2006], hardness [Zhang et al 2004], fracture toughness [Tanaka et al 2003], and creep properties [Wen et al 2006]. Indentation has several advantages over other mechanical property testing methods, as it can be easily carried out on small specimens with minimum sample preparation [Sastry 2005a].…”
Section: Introductionmentioning
confidence: 99%